Correlation analysis of gastrointestinal microbiota with IL-6 and PCNA. - Yingying Chen (500738) (2025)
(A) Correlation analysis of gastrointestinal microbiota with IL-6; (B) Correlation analysis of gastrointestinal microbiota with PCNA. Correlation analysis was conducted using Spearman’s method for statistical analysis. n = 6. *P < 0.05, **P < 0.01.